Large strain, high rate semi‐solid deformation of high density polyethylene at elevated temperatures. Issue 9 (7th October 2017) - McKelvey, D.; Menary, G.H.; Martin, P.J.; Yan, S.
Abstract : High density polyethylene (HDPE) is predominately processed from the molten state. However, there is the potential to enhance the mechanical properties by forming below the melt temperature, in the semi‐solid phase. To further investigate this enhancement, HDPE sheets were deformed under constant width, simultaneous equal‐biaxial (EB), and sequential biaxial deformation. The samples were deformed at strain‐rates, from 4 to 16 s −1, up to nominal strains of 3.0 at temperatures below 130°C. The strain‐rate and high‐strain level applied were chosen so that the data was comparable to the thermoforming process. It was discovered that in order for the HDPE sheet to deform at the high‐rate and high strains the processing temperature must be between 126°C and 130°C. This resulted in a processing window that was particularly small, 5°C, and that within this window a temperature change of 1°C had a significant impact on the stress–strain response. The samples were analyzed post deformation, where the elastic modulus was found to increase by a factor of 2.08 in the machine direction, when deformed via EB at 129°C. The results showed that HDPE can be deformed to strain levels comparable to the thermoforming process. POLYM. ENG. SCI., 58:1516–1522, 2018. © 2017 Society of Plastics Engineers